Application of rRNA-based probes for observing marine nanoplanktonic protists. - Lim, E L (1993)
The use of small-subunit rRNA-based oligonucleotides as probes for detecting marine nanoplanktonic protists was examined with a ciliate (an Uronema sp.), a flagellate (a Cafeteria sp.), and mixed assemblages of protists from enrichment cultures and natural seawater samples. Flow cytometry and epifluorescence microscopy analyses demonstrated that hybridizations employing fluorescein-labeled, eukaryote-specific probes intensely stained logarithmically growing protists, whereas these same protist strains in late stationary growth were barely detectable. The fluorescence intensity due to probe binding was significantly enhanced by the use of probes end labeled with biotin, which were detected by fluorescein-labeled avidin. The degree of signal amplification ranged from two- to fivefold for cultured protists in both logarithmic and stationary growth phases. Mixed assemblages of heterotrophic protists from enrichment cultures were also intensely labeled by rRNA-targeted oligonucleotide probes by the biotin-avidin detection system. Protists in late stationary growth phase and natural assemblages of protists that were otherwise undetectable when hybridized with fluorescein-labeled probes were easily visualized by this approach. In the latter samples, hybridization with multiple, biotin-labeled probes was necessary for detection of naturally occurring marine protists by epifluorescence microscopy. The signal amplification obtained with the biotin-avidin system should increase the utility of rRNA-targeted probes for identifying protists and facilitate characterization of the population structure and distribution of protists in aquatic environments.